To solve this system of equations, we can use the method of substitution.
From the first equation, we have:
-7x + 6y = -1
-> 6y = 7x - 1
-> y = (7/6)x - 1/6
Now substitute this expression for y into the second equation:
-7x - 3((7/6)x - 1/6) = -10
-7x - (21/6)x + 3/6 = -10
-7x - 21x/6 + 3/6 = -10
-7x - 7x/2 + 1/2 = -10
-14x - 7x + 1 = -20
-21x + 1 = -20
-21x = -21
x = 1
Now substitute the value of x back into the first equation to solve for y:
-7(1) + 6y = -1
-7 + 6y = -1
6y = -6
y = -1
Therefore, the solution to the system of equations is x = 1 and y = -1.
-7x+6y=-1 -7x-3y=-10
1 answer